2004
DOI: 10.1002/adma.200400319
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecule‐Assisted Reduction in the Synthesis of Single‐Crystalline Tellurium Nanowires

Abstract: are both localized on the substituted side fluorene groups), a sizeable increase in electron affinity (by~0.91 eV) is achieved in poly-S-m-Br-methoxy in comparison to S-methoxy. Such donor±acceptor molecular systems might not be appropriate for blue-light emission: the triplet energy is indeed bounded upwards by that of the substituted units, which itself relates to the donor/acceptor strengths (hence only weak electroactive groups, translating into small changes in HOMO±LUMO energies, will ensure high singlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
92
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 29 publications
3
92
0
Order By: Relevance
“…23 Komarneni and co-workers demonstrated a biomolecule, alginic acid, assisted synthesis of Te nanowires. 24 Zhu et al reported the microwave assisted synthesis of Te nanorods and nanowires. 25 Recently, He et al demonstrated the growth of shuttlelike scrolled tellurium nanotubes and nanowires in a wet chemical method using amino acids as a growth assisting agent.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…23 Komarneni and co-workers demonstrated a biomolecule, alginic acid, assisted synthesis of Te nanowires. 24 Zhu et al reported the microwave assisted synthesis of Te nanorods and nanowires. 25 Recently, He et al demonstrated the growth of shuttlelike scrolled tellurium nanotubes and nanowires in a wet chemical method using amino acids as a growth assisting agent.…”
Section: Introductionmentioning
confidence: 99%
“…This anisotropic structure induces Te toward 1D growth. 3,[21][22][23][24][25][26][27][28][29][30][31][32] Mayer and Xia reported the synthesis of Te nanotubes with hexagonal cross sections by reducing orthotelluric acid in ethylene glycol. 3 Wei et al synthesized Te nanotubes by a solvothermal process using N,N-dimethylformamide as a solvent and porous silica (MCM-41) as a growth assisting agent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanoparticles exhibit significantly different properties relative to those of their corresponding bulk materials. Recently, much effort has been focused on preparing t-Se and t-Te nanorods [12,13], nanowires [14][15][16][17][18], nanobelts [19,20] and nanotubes [21,22]. In this article, we report a simple hydrothermal method for direct growth of selenium and tellurium nanorods by using glucose as a green reducing agent, Na 2 SeO 3 and Na 2 TeO 3 as selenium and tellurium source, and cationic surfactant cetyltrimethylammonium bromide (CTAB) as a structure-directing agent.…”
Section: Introductionmentioning
confidence: 99%